Skin fold: Localization and procedures - A.F. Machado (Desafio Singular, 2008)
The skin fold method, also known as indirect method, utilized regression equations to predict body fat, where it is based on the relation between subcutaneous fat, internal fat and body density. However its use requires a long period of training from the appraisers, so that the results can be trusted. An important limitation on this method utilization is the difficult in standardizing measure points by the appraisers and the proceedings adopted during the process of evaluation. According to this, this study's objective was to executed a review about the localization points to the skin fold mensuration and also about the adopted proceedings during the evaluation process to minimize the errors. Initially we studied the method trusty and after that the mensuration equipments, the proceedings and the skin fold mensuration localizations. Concluding that one of the requisites to be a good appraiser of skin fold is the knowledge of the repair points and proceedings adopted to get each skin fold are also too important to the measure success.